2022
DOI: 10.3390/nu14194060
|View full text |Cite
|
Sign up to set email alerts
|

Association between Plasma Omega-3 and Handgrip Strength According to Glycohemoglobin Levels in Older Adults: Results from NHANES 2011–2012

Abstract: Background: Low muscle strength is a predictor of mortality in older adults. Although the evidence concerning hyperglycemia is limited, evidence shows that omega-3 (ω-3) intake may be positively associated with muscle strength. However, the association between plasma ω-3 and muscle strength in older adults according to glycohemoglobin (HbA1c) levels has not yet been investigated. Objective: To evaluate whether plasma ω-3 levels are associated with handgrip strength in individuals over 50 years according to HbA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…In the lipidic modulation profile, decreased HCY, 3-NT, MDA, IL-6, CRP and mtDNA copy number, or increased SOD, CAT, GRd and GPx, resulted after the physical training intervention at different intensities applied for 6-8 weeks for 75 min/week, 150 min/week or 5.5-30 MET hours/week. Increased functional autonomy, quality of life and enhanced cognitive capacities, including neurocognitive parameters, were monitored using MMSE, COWAT, DS, CDT, TMT, METS, LOTCA and GPAQ scores [12,14,17,21,22,32,35,37,38,49]. Endurance or resistance training were another form of physical activity, using devices such as a treadmill, cycle ergometer or handgrip dynamometer, being applied 6-12 weeks for 60 min/session, 3 times/week.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the lipidic modulation profile, decreased HCY, 3-NT, MDA, IL-6, CRP and mtDNA copy number, or increased SOD, CAT, GRd and GPx, resulted after the physical training intervention at different intensities applied for 6-8 weeks for 75 min/week, 150 min/week or 5.5-30 MET hours/week. Increased functional autonomy, quality of life and enhanced cognitive capacities, including neurocognitive parameters, were monitored using MMSE, COWAT, DS, CDT, TMT, METS, LOTCA and GPAQ scores [12,14,17,21,22,32,35,37,38,49]. Endurance or resistance training were another form of physical activity, using devices such as a treadmill, cycle ergometer or handgrip dynamometer, being applied 6-12 weeks for 60 min/session, 3 times/week.…”
Section: Discussionmentioning
confidence: 99%
“…Along with omegA-3, a reduced mitochondrial DNA copy number (mtDNAcn) is considered an oxidative stress biomarker and may improve muscle strength. Omega-3 intake enhances synaptic transmission at the end plate, and it also modulates the contractility of the striated muscle fibre and strength muscle [37,38]. The vitamin B group (vitamin B6, vitamin B12, folate) is associated with a decline in mental disorders and dementia by decreasing HCY trans-sulphuration or re-methylation.…”
Section: Nutraceutical Compounds/toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary omega-3 fatty acid levels are negatively associated with sarcopenia ( 104 ), and more than 2 g/day of omega-3 fatty acids may increase muscle mass and improve walking speed, especially for those with sarcopenia who have been receiving the intervention for more than 6 months ( 105 ). However, linear regression analysis concluded that there was no association between plasma omega-3 levels and grip strength in older adults ( 106 ). When cancer patients were supplemented with omega-3 fatty acids, their muscle maintenance, quality of life, and body weight were not improved ( 107 ).…”
Section: Nutritional Intervention For Sarcopeniamentioning
confidence: 99%
“…Mixed findings have been reported from recent cohort studies regarding the association between LCn-3 PUFA intake and muscle outcomes related to sarcopenia [15][16][17]. For instance, exploratory analysis of the ENHANce RCT [18] found a positive correlation between erythrocyte docosahexaenoic acid (DHA) level/omega-3 index and appendicular lean mass in a cohort of people with sarcopenia.…”
Section: Cohort Studiesmentioning
confidence: 99%